VISUALISASI TETESAN AIR MENGGUNAKAN LATTICE BOLTZMANN - Arifiyanto Hadinegoro (Universitas Sarjanawiyata Tamansiswa, 2016)
Â Water is the important element in of live, every day met with the water, Water is a chemical element that is easily deformed, many factors influence began from nature of the water itself until gravity ,the laws of physics is also present in water droplets phenomenon One such the law of force. the unique nature the water is fairly difficult for computer engineering. However With the development of computer technology now can make a visualization that is similar to the events nature. like this techniques has been apply in making movies and also games, some are used for visual effects that could not be created a real. In this study, authors try to visualize the water droplets with a fluid with one method LatticeBoltzmann fairly simple and powerful in accuracy. Visualization is made a water droplet falling on a cross-section due to gravity at work.